STRATEGY FOR SUSTAINABLE SMART TOURISM VILLAGE DEVELOPMENT IN PONGGOK VILLAGE, KLATEN, CENTRAL JAVA - Priyambodo, Tri Kuntoro; Artianingsih, Mahasika Dian (Politeknik Pariwisata NHI Bandung, 2022)
The development of ever-more-advanced technologies has led to intense competition in the tourism industry. The application of the Smart Tourism Village model is relatively new and has not been adequately realized in comparison to the already adopted Smart City concept. Ponggok Village is one of the communities that utilizes the Smart Tourism Village model by employing technology to establish the community as a tourist destination. The development of a tourist village using the Smart Tourism Village model is a solution for the development of a village; with the application of this model, quality tourism activities can be created, which can have a positive effect on community welfare and competitiveness, as well as lead to the sustainability principle in tourism development. The purpose of this study is to examine the strategy for establishing a smart tourism village and its role in achieving a sustainable tourism village in Ponggok Village, Klaten, Central Java. This study is a qualitative descriptive investigation employing SWOT analysis. Observations on the field, interviews with pertinent sources, and documentation on the subject of study were used to conduct the research. Through this research, it is anticipated that studies will be produced in the form of village development with a smart tourism village model that leads to sustainable tourism villages, as well as the advantages and disadvantages of its application, so that recommendations can be made to relevant stakeholders.